Concentration spatiale des accidents de la route : méthode d'identification des zones noires basée sur l'autocorrélation spatiale application et étude de sensibilité - Benoît Flahaut (Unité Mixte de Recherche 8504 Géographie-cités, 1999)
The objective is to identify places of spatial concentration of road accidents by black zones rather than blackspots. The application of a geographical analysis method based on local measures of spatial autocorrelation permits to localise black zones.The relevance of the method is considered; a sensibility study of the results to several contiguity levels and to several weight functions is proposed. Results are also compared to those obtained with a statistical method of smoothing (based on kernel estimators).The application of the method to some roads shows its appropriation to the problem of black zones identification.